1998
DOI: 10.3109/10826089809056249
|View full text |Cite
|
Sign up to set email alerts
|

Retention in an Aftercare Program for Recovering Women

Abstract: Examining the correlates of aftercare participation is critical to program development and successful relapse prevention. This study assesses retention in an aftercare program of case management and peer support for formerly homeless recovering mothers. Length of residential drug treatment, length of sobriety, strong support networks, and concerns about housing and parenting predicted completion of the case management component. Emotional instability and the severity of problems were found to be correlated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 20 publications
0
17
0
Order By: Relevance
“…Scott-Lennox et al (2000) found that women who had received prior residential care from the same agency as their outpatient treatment were more likely to complete the outpatient treatment. Coughey et al (1998) found that clients who had received residential treatment were more likely to complete the aftercare program than those who had not received residential treatment. The aftercare program case managers stated that women with unstable conditions or inadequate prior drug treatment were most likely to drop out and that those women should receive bfirst careQ prior to aftercare.…”
Section: Residential Treatment and Retention/other Outcomesmentioning
confidence: 96%
“…Scott-Lennox et al (2000) found that women who had received prior residential care from the same agency as their outpatient treatment were more likely to complete the outpatient treatment. Coughey et al (1998) found that clients who had received residential treatment were more likely to complete the aftercare program than those who had not received residential treatment. The aftercare program case managers stated that women with unstable conditions or inadequate prior drug treatment were most likely to drop out and that those women should receive bfirst careQ prior to aftercare.…”
Section: Residential Treatment and Retention/other Outcomesmentioning
confidence: 96%
“…Sociodemographic variables were identified as significant correlates of dropping out in some longitudinal studies (Cooney et al, 1988;Snow et al, 1992aSnow et al, , 1992b, whereas sociodemographic characteristics were not related to retention in other studies (Coughey et al, 1998). In general, attrition causes a more homogeneous sample that under-represents both drug-users and disadvantaged subjects.…”
Section: Impacts On External Validitymentioning
confidence: 98%
“…This type of support has been shown to reduce hospitalizations, substance abuse, crises interventions, improved employment outcomes, and quality of life (Coughey, 1998;Gates & Akabas, 2007). The peer worker also reports benefi ts related to being part of the team; however, proper support is important for success, including clarity of roles, policies specifi c to confi dentiality, and ethical conduct and adequate support (Gates & Akabas, 2007;Weissman et al, 2005).…”
Section: Key Characteristics For Successmentioning
confidence: 96%
“…This can be particularly important for aboriginal people, providing opportunity for culturally appropriate experiences and healing approaches (Fiske, 2008). Further more, building and extending a social support network will help ensure sustainability once formal case management has ceased (Coughey, 1998;Mueser, Bond, Drake, & Resnick, 1998).…”
Section: Key Characteristics For Successmentioning
confidence: 99%